2022
DOI: 10.1177/09603271221102508
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-455-3p from BMMSCs prevents cardiac ischemia-reperfusion injury

Abstract: Objective Bone marrow mesenchymal stem cells (BMMSCs) exert protective effects against myocardial infarction (MI). Here, we focused on the function and mechanism of miR-455-3p from BMMSCs-derived exosomes (BMMSCs-Exo) in myocardial infarction. Materials and methods BMMSCs were isolated from rat bone marrow, and the exosomes from the culture medium of BMMSCs were separated, and administered to H9C2 cells under hypoxia-reperfusion (H/R) stimulation. MTT and TUNEL staining analyzed cell viability and apoptosis, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…MiR-146-5p was demonstrated to inhibit pro-inflammatory pathways in sepsis [ 58 ] and accelerate diabetic wound healing [ 59 ]. MiR-455-3p was revealed to attenuate LPS-induced injury in bronchial epithelial cells [ 60 ] and prevent cardiac ischemia-reperfusion injury [ 61 ]. MiR-133a was also reported to have a protective effect on sepsis-induced kidney injury [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-146-5p was demonstrated to inhibit pro-inflammatory pathways in sepsis [ 58 ] and accelerate diabetic wound healing [ 59 ]. MiR-455-3p was revealed to attenuate LPS-induced injury in bronchial epithelial cells [ 60 ] and prevent cardiac ischemia-reperfusion injury [ 61 ]. MiR-133a was also reported to have a protective effect on sepsis-induced kidney injury [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-369-3p, miR-644-5p, and miR-125b-5p in MSCs-Exos exert antiapoptotic effects by inhibiting the activation of p53 [ 32 , 55 57 ]. And interestingly, miR-455-3p and miR-19a exhibit antiapoptotic effects by inhibiting JNK and subsequent activation of p53 and caspase-3 [ 58 , 59 ]. Additionally, MSCs significantly alleviate cisplatin-induced toxicity and improve islet viability by inhibiting p38/MAPK pathway [ 46 , 60 62 ].…”
Section: Mscs Protect Cells From Apoptosismentioning
confidence: 99%
“…Second, genetically modified sEVs have shown good potential for IHD treatment. For example, using miR-455-3p, miR-30e, or miR-29c-transfected sEVs could protect myocardial infarction in rodent model ( Li et al, 2020 ; Pu et al, 2021 ; Botello-Flores et al, 2022 ; Wang and Shen, 2022 ), as well as cardioprotective gene-transfected EVs, such as overexpress MIF ( Liu et al, 2020 ), or FNDC5 ( Deng et al, 2020 ), showed better therapeutic efficiency than unmodified EVs. Finally, EVs derived from some drug-pretreated MSCs can promote therapeutic effects; for example, atorvastatin-pretreated BMMSC-derived EVs enhanced therapeutic efficacy for the treatment of acute myocardial infarction by elevating lncRNA-H19 ( Huang et al, 2020 ).…”
Section: Current Progress In Improving Bmmsc-sev Efficiencymentioning
confidence: 99%